Macroamylasaemia and selective IgA deficiency. Issue 7 (July 1986) - Catassi, C; Guerrieri, A; Natalini, G; Busco, F; Giorgi, P L
Abstract : Macroamylasaemia and selective IgA deficiency were diagnosed in a 2 year old child who presented with persistent hyperamylasaemia. Macroamylasaemia is an isolated biochemical abnormality caused by aggregation of serum amylase activity with immunoglobulins. Early recognition of macroamylasaemia is important to avoid diagnosing pancreatic disease.